Non-Financial Reporting Berbasis Gri Dalam Konteks Sustainability - Cahayu Prildana Harefa; Via Mustika Irawan (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
The development of sustainability practices has encouraged companies to focus not only on financial performance reporting but also on non-financial performance that reflects economic, environmental, social, and governance (ESG) impacts. One of the most widely used non-financial reporting frameworks globally is the Global Reporting Initiative (GRI). This article aims to comprehensively examine the evolution of GRI-based non-financial reporting, covering the historical development of GRI standards, changes in reporting approaches, GRI's strategic role in promoting corporate sustainability practices, and ongoing challenges and implementation gaps. The method used is a descriptive-analytical literature review, referring to GRI standards, corporate sustainability reports, and related academic research. The results of the discussion indicate that GRI has transformed from voluntary guidelines into a global standard that functions not only as a reporting tool but also as an instrument for strategic sustainability management.